Inflammaging and the Skin - Pilkington, Suzanne M; Bulfone-Paus, Silvia; Griffiths, Christopher E M; Watson, Rachel E B (Journal of investigative dermatology, 2021)
As global life expectancy continues to rise, we are challenged with maintaining health into old age. One strategy is to target the chronic low-level inflammation associated with aging, termed inflammaging. This is characterized by increased levels of circulating proinflammatory cytokines and a shift toward cellular senescence, changes that are believed to drive many age-associated conditions, including dementia, arthritis, and type 2 diabetes. As with other organs, the skin undergoes functional decline during aging, becoming more fragile and susceptible to infection; however, the contribution of inflammaging is not well-understood. This review article describes the evidence for inflammaging in the skin, its relationship with senescence, and how this relates to declining skin structure and function.